DETEKSI DINI MASALAH GANGGUAN JIWA BERSAMA KADER KESEHATAN JIWA DI KELURAHAN TANJUNG RIAU SEKUPANG BATAM - Mira Agusthia; Rachmawaty M. Noer; Rizki Sari Utami Muchtar (Universitas Majalengka, 2020)
With the early detection of mental disorders can increase knowledge and change the attitudes and behavior of people about mental disorders. This aims to prevent mental disorders in the community. This community service method uses lecture, question and answer discussion and also a direct examination of mental disorders carried out by mental health program holders together with mental health cadres in Outahan Tanjung Riau Sekupang. The material provided in this activity in the form of the importance of detecting early mental disorders by knowing the definition, you and the symptoms and causes of mental disorders. The results of community service have a positive impact which is very beneficial for the people in the Tanjung Riau Outflow because it can add insight to the early detection of mental disorders and this activity also provides information to the public about the importance of conducting mental health checks on health services.